Transcriptome profiling of flax plants exposed to a low-frequency alternating electromagnetic field - Kostyn, Kamil; Boba, Aleksandra; Kozak, Bartosz; Sztafrowski, Dariusz; Widuła, Jan; Szopa, Jan; Preisner, Marta (Frontiers in Genetics, 2023)
All living organisms on earth evolved in the presence of electromagnetic field (EMF), adapted to it, and even learned to use it for their purposes. However, during the last century the earth’s core lost its exclusivity and a number of sources of the EMF appeared due to the development of electricity and electronics. Previous research suggested that EMF led to changes in the intercellular free radical homeostasis and further in altered expression of genes involved in plant’s response to environmental stresses, in inorganic ion transport and cell wall constituent biosynthesis. Later, a CTCT sequence motifs in gene promoters were proposed to be responsible for the response to EMF. It remains unknown how these motifs or different mechanisms are involved in the plants’ reaction to external EMF. Moreover, as many genes that are activated under EMF treatment do not have the CTCT repeats in their promoters we decided to determine the transcription profile of a plant exposed to EMF and pinpoint the genes that directly response to the treatment to find the common denominator of the observed changes in plant’s transcriptome.